Case report: Regression of Glioblastoma after flavivirus infection - Garcez, Patricia P.; Guasti, André; Ventura, Nina; Higa, Luiza Mendonça; Andreiuolo, Felipe; de Freitas, Gabriella Pinheiro A.; Ribeiro, Liane de Jesus; Maia, Richard Araújo; de Lima, Sheila Maria Barbosa; de Souza Azevedo, Adriana; Schwarcz, Waleska Dias; Caride, Elena Cristina; et al. (Frontiers in Medicine, 2023)
Glioblastoma is the most frequent and aggressive primary brain cancer. In preclinical studies, Zika virus, a flavivirus that triggers the death of glioblastoma stem-like cells. However, the flavivirus oncolytic activity has not been demonstrated in human patients. Here we report a glioblastoma patient who received the standard of care therapy, including surgical resection, radiotherapy and temozolomide. However, shortly after the tumour mass resection, the patient was clinically diagnosed with a typical arbovirus-like infection, during a Zika virus outbreak in Brazil. Following the infection resolution, the glioblastoma regressed, and no recurrence was observed. This clinical response continues six years after the glioblastoma initial diagnosis.